2010
DOI: 10.1007/s10571-009-9490-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Actions of the Synthetic Estrogen 17α-Ethynylestradiol in the Hippocampus

Abstract: 17alpha-ethynylestradiol (EE2), a major constituent of many oral contraceptives, is similar in structure to 17beta-estradiol, which has neuroprotective properties in several animal models. This study explored the potential neuroprotective actions of EE2 against kainic and quinolinic acid toxicity in the hippocampus of adult ovariectomized Wistar rats. A decrease in the number of Nissl-stained neurons and the induction of vimentin immunoreactivity in astrocytes was observed in the hilus of the dentate gyrus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Progesterone could exert its anticonvulsant effect in the zebrafish embryo as a result of its conversion to allopregnanolone, as has been observed in mice (Reddy et al, 2004). Our discovery of an anticonvulsant effect for ethinyl estradiol is intriguing because this drug is known to reduce aggression and reproductive success in zebrafish (Colman et al, 2009) and it is neuroprotective against kainic-acid-induced excitotoxicity (Picazo et al, 2010), but it has not previously been shown to stimulate inhibitory neurotransmission as a GABA A receptor agonist or to act as an anticonvulsant. Nevertheless, ethinyl estradiol was a more potent inhibitor of PTZ-induced locomotor activity than was allopregnanolone, raising the possibility that it might have an inhibitory effect on movement that could be independent of, and in addition to, an interaction with the GABA A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone could exert its anticonvulsant effect in the zebrafish embryo as a result of its conversion to allopregnanolone, as has been observed in mice (Reddy et al, 2004). Our discovery of an anticonvulsant effect for ethinyl estradiol is intriguing because this drug is known to reduce aggression and reproductive success in zebrafish (Colman et al, 2009) and it is neuroprotective against kainic-acid-induced excitotoxicity (Picazo et al, 2010), but it has not previously been shown to stimulate inhibitory neurotransmission as a GABA A receptor agonist or to act as an anticonvulsant. Nevertheless, ethinyl estradiol was a more potent inhibitor of PTZ-induced locomotor activity than was allopregnanolone, raising the possibility that it might have an inhibitory effect on movement that could be independent of, and in addition to, an interaction with the GABA A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective actions of other estrogenic compounds, including contraceptives [71], ligands for nonclassical estrogen receptors [5,14] and non-feminizing estrogens [72], have been explored in animal models with promising results. Further developments may include the use of aromatase modulators to selectively increase brain estradiol synthesis as an alternative to the administration of estrogenic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The same dose of a scrambled missense oligo (MS; 5′‐ATCGTGGATCGTGAC‐3′) was used as control. To stimulate estrogen‐signaling, rats were injected with a single bolus of E 2 (5 μg; oil‐vehicle; Sigma, St. Louis, MO, USA) or estrogenic component of OC ethinyl estradiol (EE; 5 μg; oil‐vehicle; concentration based on Picazo et al. 2011) on the second day (48 h prior to killing the rats) of AS treatment.…”
Section: Methodsmentioning
confidence: 99%